Mechanical Testing and Modeling of Interlayer Bonding in HMA Pavements. Issue 11 (November 2019) - Leischner, Sabine; Canon Falla, Gustavo; Gerowski, Bettina; Rochlani, Mrinali; Wellner, Frohmut
After premature de-bonding failures of several roads in Germany, researchers at the Technische Universität Dresden developed a new testing device, the Dresden Dynamic Shear Tester (DDST), for quality control and characterization of the interlayer bond. The DDST is used to quantify the shear stiffness of the interlayer bond between asphalt layers at different temperatures, stress levels, and frequencies. The DDST was designed to avoid some limitations of common interlayer bond static tests (i.e., Leutner tests, torque bond tests, etc.) by simulating the dynamic loads experienced by real pavements and determining material parameters which can be used within mechanistic models. The paper presents the philosophy and methodology behind the DDST as well as the post-processing of the test data to obtain a master curve of shear stiffness of the interlayer bond. The master curve is determined by back-calculation of testing data by coupling a Fourier assisted finite element method with an optimization algorithm. The results of experiments showed that the shear stiffness at the interlayer zone was strongly influenced by the temperature, frequency, and normal load. At high temperatures the adhesion of the tack coat did not contribute to the layer bond. It was deduced that at high temperature and with no axial load shear stiffness was achieved only through aggregate interlocking and, when normal pressure was applied, through friction between the surfaces of the asphalt layers.